Age-Related Eye Diseases and Visual Impairment Among U.S. Adults - Chou, Chiu-Fang (2013)
BACKGROUND: Visual impairment is a common health-related disability in the U.S. The association between clinical measurements of age-related eye diseases and visual impairment in data from a national survey has not been reported. PURPOSE: To examine common eye conditions and other correlates associated with visual impairment in the U.S. METHODS: Data from the 2005–2008 National Health and Nutrition Examination Survey of 5222 Americans aged ≥40 years were analyzed in 2012 for visual impairment (presenting distance visual acuity worse than 20/40 in the better-seeing eye), and visual impairment not due to refractive error (distance visual acuity worse than 20/40 after refraction). Diabetic retinopathy (DR) and age-related macular degeneration (AMD) were assessed from retinal fundus images; glaucoma was assessed from two successive frequency-doubling tests and a cup-to-disc ratio measurement. RESULTS: Prevalence of visual impairment and of visual impairment not due to refractive error was 7.5% (95% CI=6.9%, 8.1%) and 2.0% (1.7%, 2.3%), respectively. The prevalence of visual impairment not due to refractive error was significantly higher among people with AMD (2.2%) compared to those without AMD (0.8%), or with DR (3.5%) compared to those without DR (1.2%). Independent predictive factors of visual impairment not due to refractive error were AMD (OR=4.52, 95% CI=2.50, 8.17); increasing age (OR=1.09 per year, 95% CI=1.06, 1.13); and less than a high school education (OR=2.99, 95% CI=1.18, 7.55). CONCLUSIONS: Visual impairment is a public health problem in the U.S. Visual impairment in two thirds of adults could be eliminated with refractive correction. Screening of the older population may identify adults at increased risk of visual impairment due to eye diseases.